Macular pseudohaemorrhage secondary to Allen Dot artefact. (5th January 2015) - Michaels, Luke; Alexander, Philip; Newsom, Richard
Abstract : A 34-year-old highly myopic (−11.00 D) woman presented to eye clinic with a 3 day history of right eye paracentral blurring. Visual acuities were 6/6 bilaterally. Clinical examination was normal. Fundus photography showed the classic appearance of a macular haemorrhage. This is a recognised complication of high myopia and would have accounted for the patient's symptoms. However, further photography showed that the haemorrhage seemed to 'jump' around the fundus and was even present in the fellow eye. The apparent haemorrhage was revealed to be an imaging artefact. The 'Allen Dot' is a 6 mm black mask incorporated into retinal cameras to reduce reflection. Rarely, in highly myopic eyes, optical artefact can result. To the best of our knowledge, we are the first in the literature to report artefacts from the Allen Dot masquerading as ophthalmic disease. This case re-iterates the importance of clinical examination, especially in high myopes, given the current trend towards virtual clinics.